The Effect of Multiple Hop and Jump Exercises on Blocking Jump Height in Women's Volleyball Extracurriculars North Bengkulu State Vocational School 5 - Arwin; Rahmat Rilo Pambudi; Defliyanto Defliyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This study aims to determine how much influence the multiple hop and jump exercises have on the height of the blocking jump in the women's volleyball extracurricular at SMK Negeri 5 Bengkulu Utara. The type of research used in this research is experimental research using the one group pre test – post test design. The population in this study were all female volleyball extracurricular participants at SMK Negeri 5 North Bengkulu, totaling 25 athletes. The results of the study The effect of multiple hop and jump exercises on the height of the blocking jump in the women's volleyball extracurricular at SMK Negeri 5 Bengkulu Utara has an increase with a percentage of 11.7% and the results of the tcount test = 3.72 > t table = 1.711. it can be concluded that the multiple hop and jump exercises affect the height of the blocking jump.